The Effect of Emitter Spacing on Physical Clogging of Drip Irrigation Tapes - C. Abdi; P. Fathi (علوم آب و خاک, 2017)
Drip irrigation is one of the new irrigation methods for optimum use of water resources and increase of irrigation efficiency. The emitterschr('39') clogging is the most important problem in these systems. The physical clogging is the most important factor in reducing the discharge and emission uniformity of emitters. The emitter position on the laterals and emitter spacing are the factors that affect the physical clogging rate of emitters. The objective of the present study is evaluating the effect of emitter spacing of drip irrigation tape on the physical clogging rate of emitters. For this purpose, a physical model of drip irrigation tape was designed and made at the laboratory. In this research, seamless and seamed irrigation tapes with emitter spacing equal to 10, 20 and 30 centimeters were used. Statistical analysis showed that emitters spacing have significant effect on clogging rate of emitters in seamless and seamed drip irrigation tapes. The results also indicated that seamless irrigation tapes with 30-centimeter emitters spacing, with clogging rate of 22 percent, have the least clogging. A comparison of clogging rate and uniformity coefficient of irrigation tape showed the higher performance of seamless irrigation tape in clogging condition.